Is Isaiah's "servant covenant" the new covenant? : an exegetical study - Fredrickson, David K. (Lewiston ; Lampeter : The Edwin Mellen Press, 2014)
""Fredrickson's work is fresh, engaging and foundational for those who embrace the blessings of the New Covenant. His careful exegesis of the relevant new Covenant texts makes his book an especially helpful resource ... this book would be warmly welcomed by biblical scholars, theologians and serious minded pastors. [It] is a significant contribution to the study of the New Covenant and the question of whether the New Covenant is referred to in Isaiah's Servant Songs.- Professor J. Carl Laney, Western Seminary, Oregon.
Includes bibliographical references and index.
Print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Isaiah -- Criticism, interpretation, etc; Bible. -- Isaiah; Bible; Covenants -- Biblical teaching; Covenants -- Biblical teaching; RELIGION -- Biblical Studies -- Prophets; Covenants -- Biblical teaching; Electronic books; Criticism, interpretation, etc